An interval risk assessment method and management of water inflow and inrush in course of karst tunnel excavation. (October 2019) - Wang, Xintong; Li, Shucai; Xu, Zhenhao; Li, Xiaozhao; Lin, Peng; Lin, Chunjin
Abstract: An interval risk assessment method of water inflow and inrush in karst tunnel is proposed. Based on the method, both a conceptual and a computational form of the risk assessment model is introduced, and risk surroundings, construction factors and feedback information are analyzed. The conceptual model consists of three hierarchies and three stages. Thirteen factors were chosen as assessment indices and can be grouped into three categories: karst hydrogeological conditions and geological engineering conditions, construction factors and feedback information for management. An analytic hierarchy process and fuzzy mathematical theory were used to develop a computational model based on the interval number. The interval membership function and the weight of each factor were quantified and a relative superiority analysis of the interval matrix was performed. Moreover, a construction permission mechanism of water inflow and inrush in karst tunnels was established. In the present study, the three-stage risk assessment model and construction permission mechanism were successfully applied to the Qiyueshan tunnel. Thus, the interval risk assessment method may provide a practical reference for the risk assessment and management of karst tunnel construction and is worth exploring to control risk in other engineering construction projects.